Systematic analysis of the factors that impact upon the mindset of knowledge sharing behaviour (KSB) for individuals within academia - Khalid Mahmood Abbas; Ahmed Eltweri; Muhammad Kamran Nawaz; Zafar Ali (Administrative Sciences, 2023)
The aim of this study is to provide an examination of the factors that have a bearing on KSB, based upon attitudes amongst academics in developing countries, using a particular focus upon academics within the University of Baghdad. With the research study, structural equation modelling was undertaken by using a questionnaire survey for examination of attitudes to microfoundations with regard to KSB amongst a total of 326 academics based at the University of Baghdad. With regard to KSB, it was found that three of the hypothesised factors (anticipation of extrinsic rewards, anticipation of reciprocal relationships and perception of reciprocal benefits) were significantly and positively related. No significant relationship, however, was found to exist between KSB and interpersonal interactions. Based upon the results, a refined, valid model succeeds in exhibiting good explanatory power for the prediction of the intentions for the KSB of academics. Furthermore, it was suggested by the results that academics who were less educated had a greater willingness for knowledge sharing than those who were more highly educated. Based upon the unprecedented data, the paper makes a contribution to growing KSB-theory-related research, particularly with respect to the planned model of behaviour, and puts forward empirical evidence in support of the relationship between attitude and the KSB of academics.
Keywords: 350; attitude towards knowledge sharing; higher education; knowledge management; knowledge sharing; knowledge sharing behaviour